Restoring Pedagogical Vitality: Restitching Documentation, Pedagogy, and Progettazione - Delgado Vintimilla, Cristina; Pacini-Ketchabaw, Veronica (Journal of Childhood Studies, 2025)
Pedagogical documentation has undoubtedly inspired novel and ethically responsive practices in early childhood education. However, it has also contributed to legitimizing logics that have lost their experimental vitality. This article addresses this paradox through two movements. First, the authors create a “conceptual stitch” by which to reconnect documentation, relationally and conceptually, with pedagogy and progettazione. Second, they propose four ideas for rethinking documentation through this conceptual stitch. In making these moves, the authors seek to restore documentation’s relational integrity and open space for education’s pedagogical possibilities beyond the obscure and the normative.